(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
Driven by the importance of the behavioral class of empathy and by the divergences found in the literature, Vettorazzi et al. (2005) proposed a systematization of empathic intermediary behaviors. However, this systematization followed the demands of a specific case, and gaps remain in relation to which intermediary behaviors should be part of empathy. Our purpose in this article was to review Vettorazzi et al.’s systematization and adapt it to a wider target audience by adding or adjusting intermediary behaviors. We also tried to elaborate a specific sequence for teaching these behaviors. As a result, we elaborated a new decomposition diagram with 46 intermediary behaviors and a sequencing table distributed in six teaching units. This represents an advance toward the development of behavior-analytic programs that teach emphatic behavior and that may address the needs of different target audiences.